Egypt and the Superpowers - Shafik, Nazli Talaat (AUC Knowledge Fountain, 1988)
Egypt and the superpowers [manuscript] : the domestic factors influencing alignment, 1955-1985 / Nazli Talaat Shafik. The thesis was submitted to the Department of Political Science